CircRNA protein tyrosine phosphatase receptor type a suppresses proliferation and induces apoptosis of lung adenocarcinoma cells via regulation of microRNA-582-3p. Issue 5 (2nd May 2022) - Jiang, Jixin; Ge, Hui; Yang, Jie; Qiao, Yunfei; Xu, Xingxiang; Geng, Yanming
ABSTRACT: Circular RNAs (circRNAs) are associated with cancer progression. The present study aimed to examine the function of circRNA protein tyrosine phosphatase receptor type A (circRNA_PTPRA) in lung cancer cells and elucidate the underlying molecular mechanisms. The levels of circRNA_PTPRA and microRNA (miRNA/miR)-582-3p were measured in lung cancer tissue and cells using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Cell proliferation and apoptosis were evaluated using an 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay and flow cytometry, respectively. The expression of cyclin D1, caspase-3, and cleaved caspase-3 was assessed via western blotting. The sites of circRNA_PTPRA/miR-582-3p interaction were identified using StarBase, and validated using a dual-luciferase reporter assay. We observed that circRNA_PTPRA levels were remarkably decreased, and miR-582-3p expression was up-regulated in lung cancer tissues and cells. circRNA_PTPRA directly interacts with miR-582-3p and downregulates miR-582-3p expression in lung cancer cells. Moreover, an miR-582-3p inhibitor decreased lung cancer cell proliferation and promoted apoptosis. The overexpression of circRNA_PTPRA decreased cell proliferation and increased apoptotic cell numbers, whereas miR-582-3p overexpression reversed these effects. These findings demonstrate that the up-regulation of circRNA_PTPRA significantly reduces lung cancer cell proliferation and induces apoptosis by regulating miR-582-3p expression. Graphical abstract: uf0001